Cardiometabolic risk in pre- and post-menopausal women with special reference to insulin resistance: A cross-sectional study - Utkarshini Kirtikar; Neha Kajale; Vivek Patwardhan; Vaman Khadilkar; Anuradha Vaman Khadilkar (Wolters Kluwer Medknow Publications, 2020)
Background: Reduced levels of estrogen have been associated with metabolic alterations and increased insulin resistance (IR) in postmenopausal women, thus predisposing them to cardiometabolic risks. The aim of this study was to assess alterations in parameters of cardiometabolic risk in apparently healthy pre- and post-menopausal women and to study the effect of IR on these metabolic parameters. Methods: A cross-sectional study was conducted on randomly selected apparently healthy women (n = 262). These women were categorized as premenopausal (n = 184) and postmenopausal (n = 78). Anthropometric measurements, blood pressure, lipid profile, fasting glucose, and insulin concentrations were estimated on all the participants using standard protocols. Homeostatic model assessment of IR was computed to estimate the level of IR. Results: Most lipid parameters, blood pressure, waist circumference, and fat percentage were significantly higher (P < 0.05) in postmenopausal women than premenopausal women. On subcategorizing women with respect to IR (<3, >3), metabolic parameters (e.g., triglyceride - 104.7 ±53.2 mg/dl, Blood Sugar Level Fasting (BSLF) - 103.3 ± 40.1 mg/dl, and fasting serum insulin - 23 ± 12.3 mIU/L) were also higher (P < 0.001) in premenopausal women having IR >3. Significantly higher low-density lipoprotein (132.7 ± 38.7 mg/dl vs. 114.4 ± 25 mg/dl) and total cholesterol (211.3 ± 40.5 vs. 184.8 ± 29.4 mg/dl) were observed in postmenopausal women with IR >3 (P < 0.05) along with higher BSLF (126.6±54.3 mg/dl**) and fasting insulin levels (22.3 ± 12.1 mIU/L) (P < 0.001). Conclusion: This study reveals that IR may predispose women to increased cardiometabolic risk. Urgent attention needs to be focused toward metabolic health of women.